THE EFFECTS OF WEATHER CONDITIONS ON THE HEALTH OF PEOPLE LIVING IN URBAN AND RURAL ENVIRONMENTS - Čelić, Irena; Živanović, Sandra; Pavlović, Nebojša (Economics of Agriculture, 2019)
Meteorology is an essential part of peoples lives. Its influence on every aspect of human life is vast and especially connected to the well-being of an individual. The objective of this paper is to ascertain how meteorologic changes influence the health of people who live in urban and rural environments. The testing was carried out on a sample of 130 respondents. The respondents are of different sex, age and come from various environments. This research was conducted via an anonymous questionnaire. The results point to the fact that meteorological changes affect the health and well-being of both healthy and ill individuals, whether they live in urban or rural environments. The significance of this paper is reflected in the acquiring of data that can be used in medicine as well as health tourism.